Growth control of herbaceous ground cover and egg quality from an integrated poultry-hazelnut orchard system - Cosentino, Carlo; Freschi, Pierangelo; Fascetti, Simonetta; Paolino, Rosanna; Musto, Mauro (Italian Journal of Agronomy, 2020)
The present study was designed to assess the impact of hen grazing on plant biodiversity in the ground cover of hazelnut orchards, as well as the quality of eggs from hens grazing in the orchards. Two different sites of hazelnut orchards located in Basilicata region were selected to conduct this study. The results showed that hen grazing affected the composition of herbaceous stratum of the orchards. By using the quadrat method, a total of 99 (46 in site A and 53 in site B) plant species were identified at the beginning of the trial. After hen grazing, the number of identified plants dropped to 72 (30 in site A and 42 in site B). Amongst the most consumed species we found Lolium sp., Trifolium sp., Polygonum sp., Cichorium intybus, Cynodon dactylon. Alpha diversity analysis (species richness, diversity and evenness) as well as beta diversity analysis (Morisita-Horn and Sørensen indices) confirmed that hen grazing played a role in controlling vegetation growth. Concerning egg quality, most of the chemical parameters differed significantly when comparing the eggs from the sites with those from the control group, indicating that egg quality was influenced by the food resources available in each site. Overall, our results confirm that poultry may play a positive role in an orchard system. Highlights - The impact of an integrated poultry-hazelnut orchard system on herbaceous plant species diversity and on egg quality was evaluated. - Hen grazing may benefit herbaceous ground cover biodiversity of the orchards. - Egg quality may be affected by the food resources available in the orchards.